Leadership Styles and Performance in the Merchant Marine - Wasbrum Tinoco, Wendy Esthela; Wasbrum Tinoco, Wilfrido Giovanny; Guale Sánchez, Andrea de las Mercedes; Vélez García, Gladys María (Revista Universidad de Guayaquil, 2023)
This work has been done with the intention of making known the importance of leadership not only in the field of merchant marine, but also the recognition of the fact that when societies are not dominated by a common thought which serves as the center of all intellects and when they do not recognize dogma or principle, powerful enough to give a character of unity to all their efforts, as well as to establish the desired concord among all wills, societies fall prey to an early decadence which causes difficulties in their organic life, their intellectual life is extinguished, allowing individualism to invade them; thus provoking an intimate and deep malaise not only in individuals, but also in the work group as a whole, thus reducing the efficiency of the group, of the work area, even in the same company. The design of the present study is qualitative in nature, which has an analytical scope. It was defined as analytical in nature because it seeks to relate leadership with performance, as well as the variables that make up both factors, which will be detailed in the course of this research work. The target population of this research work corresponds to the Ecuadorian Oil Fleet (Flopec), in which case interviews were conducted with the personnel that can provide us with the necessary information for the elaboration of the research. It is concluded that to increase efficiency, productivity and work effectiveness requires understanding the differences and similarities they have.
Keywords: Leadership; hampered; efforts; efficiency